The Relationship Between The Intensity Of Tahajud Prayer With Stress Levels On Ahmad Dahlan University Medical Faculty Students - Hafizh Fernanda, Muhammad; Sukaca, Agus; Rossi Desvita, Widea; Junaidy Heriyanto, Mochammad; Tejosukmono, Ario; Annisa, Annisa (Universitas Ahmad Dahlan, 2024)
Tahajud prayer is a night prayer that is performed when most people are fast asleep, in the last third of the night. Physiologically, human life has a diurnal circadian rhythm pattern. If this pattern is accompanied by the obligation to perform tahajud prayer, the circadian rhythm pattern can become nocturnal. As a result, the central nervous system undergoes behavioral changes aimed at adjusting to changes in circadian rhythms. Stress is a condition where a person's physical and psychological balance is disturbed due to a trigger and can hinder a person in carrying out their tasks. Through prayer, a person will feel close to the Creator, all tiredness, problems, burden of thoughts, and emotions, all of which are abandoned during prayer in a solemn manner. The purpose of this study is to analyze whether there is a relationship between the intensity of tahajud prayer and stress levels in students of the Faculty of Medicine, Ahmad Dahlan University Yogyakarta. The research method used in this study is an observational analytic quantitative method using a cross-sectional design. The research sample amounted to 153 students of the Faculty of Medicine, Ahmad Dahlan University. The research instruments were the Perceived Stress Scale (PSS-10) questionnaire and the Tahajud Prayer Practice questionnaire. Statistical tests using the Rank-Spearman test found a p-value of 0.000 < α (0.05) with a correlation coefficient of -0.342 and the Kendall's Tau test found a p-value of 0.000 < α (0.05) with a correlation coefficient of -0.328 indicating moderate correlation strength. The conclusion of this study is that there is an inversely proportional relationship between the intensity of tahajud prayer and stress levels in Ahmad Dahlan University Faculty of Medicine students which means that the higher the intensity of tahajud prayer, the lower the stress level tends to be, and vice versa, if the intensity of tahajud prayer is lower, stress levels tend to be higher. Therefore, it is expected that students can increase the intensity of tahajud prayer in their daily lives to reduce stress levels.